Introducing Smart Machines Technology and Netiquette for Highschool Students - Rahim, Noorfi Azizah; Djajasoepena, Rafie; Purnomo, Ariana Tulus; Setiawan, Iwan; Triawan, Farid; Bhakti, Muhammad Agni Catur; Lestari, Tika Endah; Sulistyo, Eko; Solihin, Unang; Eryanto, Ery; Wandy, Wandy (Center for Research and Community Service of Sampoerna University, 2023)
Artificial intelligence is evolving and changing what work means in industrial settings. Smart machines are replacing numerous tasks normally done by human workers. Thus, the young generation needs to be prepared and guided, making them aware of what competencies they should acquire before entering the society. The present community service activity aims to communicate the importance of understanding Smart Machines Technology and Netiquette for Highschool-Students in a public senior high school in Cirebon city, namely SMAN 6 Cirebon. A seminar about smart machines and netiquette was conducted. The young generation frequently uses social networking sites to communicate with friends. Ethics in communication must be appropriately implemented in online platforms. In parallel, a digital library system was developed in the school. Literature review, interviews with digital technology professionals, and discussions with school librarians were carried out throughout this community service activity.